Stability of Individuals’ Definitions of Success and the Influence of Perceived Motivational Climate: A Longitudinal Perspective - Nerstad, Christina G. L.; Buch, Robert; Dysvik, Anders; Säfvenbom, Reidar (Frontiers in Psychology, 2020)
In the present study we investigated the stability and malleability of cadets’ definitions of success (mastery and performance goal orientations) contextualized within a certain motivational climate (mastery and performance climates). Based on data from three military academies, the results revealed that cadets’ goal orientations and their perceptions of the motivational climate remained relatively stable throughout the two years of study across three time-points. We also found that a mastery climate predicted individual mastery orientation, and that a performance climate predicted individual performance orientation. These findings contribute to achievement goal theory by clarifying the importance of considering goal orientation contextualized within a certain motivational climate over time. Implications for future research and practice are discussed.